Therapeutic Hypothermia in Neonatal Hypoxic-Ischemic Encephalopathy: Current Evidence and Clinical Practice- A Literature Review - Trzepizur, Alicja; Spaczyńska-Kwiatkowska , Monika; Socha, Zuzanna; Ochońska , Izabela; Studziński, Dawid; Michałek, Sandra; Pakulska , Julia (Quality in Sport, 2026)
Background: Hypoxic-ischemic encephalopathy (HIE) remains a major cause of neonatal mortality and long term neurodevelopmental impairment worldwide. Therapeutic hypothermia (TH) is currently the standard of care for newborns with moderate-to-severe HIE; however, several aspects of its use remain controversial. Aim: The aim of this paper is to present the current state of knowledge regarding the use of therapeutic hypothermia in newborns with HIE with particular emphasis on mechanisms of action, eligibility criteria, course of therapy, clinical efficacy and adverse effects, as well as to discuss current controversies and directions for further research. Material and methods: A narrative literature review was conducted using the PubMed database to identify studies on therapeutic hypothermia in newborns with hypoxic-ischemic encephalopathy. Publications from the past 11 years were included with particular emphasis on studies published within the last 5 years. Relevant original articles and review papers focusing on clinical outcomes and effectiveness were analyzed. Results: Therapeutic hypothermia reduces the risk of death and severe neurodevelopmental disability in newborns with moderate and severe HIE. Its neuroprotective effects are associated with reduced cerebral metabolism, decreased oxidative stress, modulation of inflammatory response, and inhibition of apoptosis. However, its efficacy in mild HIE and in preterm infants remains inconclusive. The most common adverse effects include cardiovascular, metabolic, and hematological disturbances requiring close monitoring. Conclusions: Therapeutic hypothermia is an effective and relatively safe treatment for HIE; however, it does not completely eliminate the risk of neurodevelopmental impairment. Further research is needed to optimize treatment protocols, expand its use to other populations and evaluate combination therapies.